FAKTOR RESIKO PREEKLAMSIA PADA IBU HAMIL: LITERATURE REVIEW: FAKTOR RESIKO PREEKLAMSIA PADA IBU HAMIL: LITERATURE REVIEW - Stianto, Mitayakuna; Fatimah, Siti; fitriana, Alfira (WELL BEING, 2022)
Background: The maternal mortality rate in Indonesia in 2020 reached 462 per 100,000 live births. Preeclampsia is some specific symptoms that only appear during pregnancy at 20 weeks of gestation (except for trophoblastic problems), these symptoms include hypertension accompanied by the presence of protein in the urine. The impact of preeclampsia on pregnant women can cause a decrease in consciousness, if preeclampsia is severe it can be accompanied by seizures. The purpose of this study is to determine the risk factors that influence the occurrence of preeclampsia. Subjects and Methods: This was a literature reviews study. The articles used were obtained from PubMed, and Google Scholar. Several passwords were used: "pregnant women" OR "mothers in labor" AND preeclampsia OR eclampsia OR eclampsia AND "risk factors" OR "risk factors" This method aims to increase understanding of the topics discussed by summarizing the topics to be discussed. This method provides insight into new facts/analyses as well as a literature review providing a summary of good and relevant publications that are further compared with the results that have been presented in the article. Results: of 11 articles that met the inclusion and exclusion criteria, 8 articles with a case-control study design, 2 cross-sectional articles, and 1 retrospective cohort study article. Conclusion: Risk triggers that have a relationship with the incidence of preeclampsia include the age of pregnant women at risk for nulliparity, primigravida, economic factors, previous history of preeclampsia, parity, level, education, use of ANC, gestational period, BMI before pregnancy, history of abortion, history of hormonal contraceptive use, Heredity, Multiple pregnancies, Medical history (chronic hypertension, diabetes, kidney disease, and obesity), Hypertension, Diabetes, Obesity